Analysis of double U-tube ground heat exchanger for renewable energy applications with two-region simulation model by combining analytical and numerical techniques - Salilih, Elias M.; Abu-Hamdeh, Nidal H.; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
This research is concerned on heat transfer analysis and modelling in a double U-tube borehole heat exchanger (BHE), via dividing the borehole into two separate regions. The inner part region of the borehole was analyzed analytically, while the outer region of the borehole was studied numerically. The two analyses were joined with the borehole wall temperature. The transient heat transfer of the borehole outer region was analyzed with thermal resistance model using the implicit numerical technique. In the contrary the thermal capacitance of the inner region of the borehole was ignored in this analysis as the inner portion of the borehole is insignificant compared to the outer borehole region and its modelling was only treated with analytical method. Variation of borehole temperature with time, the variation of rate of heat transfer between the borehole inner region to the outer region, radial temperature profile of the ground, and variation in mean temperature of ground with respect to time were investigated for three borehole operation scenarios (i.e. double charging, double discharging, simulations charging and discharging).
Keywords: Borehole wall temperature; Borehole heat exchanger; Double U-tube; Numeric; Renewable energy